Azathioprine and Risk of Skin Cancer in Organ Transplant Recipients: Systematic Review and Meta‐Analysis. Issue 12 (7th July 2016) - Jiyad, Z.; Olsen, C. M.; Burke, M. T.; Isbel, N. M.; Green, A. C.
Abstract : Azathioprine, a purine antimetabolite immunosuppressant, photosensitizes the skin and causes the production of mutagenic reactive oxygen species. It is postulated to increase the risk of squamous cell carcinoma (SCC) and other skin cancers in organ transplant recipients (OTRs), but evidence from multiple, largely single‐center studies to date has been inconsistent. We aimed to resolve the issue of azathioprine's carcinogenicity by conducting a systematic review of the relevant literature and pooling published risk estimates to evaluate the risks of SCC, basal cell carcinoma (BCC), keratinocyte cancers (KCs) overall and other skin cancers in relation to azathioprine treatment. Twenty‐seven studies were included in total, with risk estimates from 13 of these studies able to be pooled for quantitative analysis. The overall summary estimate showed a significantly increased risk of SCC in relation to azathioprine exposure (1.56, 95% confidence interval [CI] 1.11–2.18). No significant associations between azathioprine treatment and BCC (0.96, 95% CI 0.66–1.40) or KC (0.84, 95% CI 0.59–1.21) risk were observed. There was significant heterogeneity between studies for azathioprine risk estimates and the outcomes of SCC, BCC and KC. The pooled findings of available evidence support the contention that treatment with azathioprine increases the risk of SCC in OTRs. Abstract : This meta‐analysis compares azathioprine with other immunosuppressants in organ transplant recipients and shows a significantly increased risk of squamous cell carcinoma in patients receiving azathioprine posttransplantation.